Estrogen receptor α dependent regulation of estrogen related receptor β and its role in cell cycle in breast cancer - B. Madhu Krishna; Sanjib Chaudhary; Dipti Ranjan Mishra; Sanoj K. Naik; S. Suklabaidya; A. K. Adhya; Sandip K. Mishra (BMC Cancer, 2018)
Abstract Background Breast cancer (BC) is highly heterogeneous with ~ 60–70% of estrogen receptor positive BC patient’s response to anti-hormone therapy. Estrogen receptors (ERs) play an important role in breast cancer progression and treatment. Estrogen related receptors (ERRs) are a group of nuclear receptors which belong to orphan nuclear receptors, which have sequence homology with ERs and share target genes. Here, we investigated the possible role and clinicopathological importance of ERRβ in breast cancer. Methods Estrogen related receptor β (ERRβ) expression was examined using tissue microarray slides (TMA) of Breast Carcinoma patients with adjacent normal by immunohistochemistry and in breast cancer cell lines. In order to investigate whether ERRβ is a direct target of ERα, we investigated the expression of ERRβ in short hairpin ribonucleic acid knockdown of ERα breast cancer cells by western blot, qRT-PCR and RT-PCR. We further confirmed the binding of ERα by electrophoretic mobility shift assay (EMSA), chromatin immunoprecipitation (ChIP), Re-ChIP and luciferase assays. Fluorescence-activated cell sorting analysis (FACS) was performed to elucidate the role of ERRβ in cell cycle regulation. A Kaplan-Meier Survival analysis of GEO dataset was performed to correlate the expression of ERRβ with survival in breast cancer patients. Results Tissue microarray (TMA) analysis showed that ERRβ is significantly down-regulated in breast carcinoma tissue samples compared to adjacent normal. ER + ve breast tumors and cell lines showed a significant expression of ERRβ compared to ER-ve tumors and cell lines. Estrogen treatment significantly induced the expression of ERRβ and it was ERα dependent. Mechanistic analyses indicate that ERα directly targets ERRβ through estrogen response element and ERRβ also mediates cell cycle regulation through p18, p21cip and cyclin D1 in breast cancer cells. Our results also showed the up-regulation of ERRβ promoter activity in ectopically co-expressed ERα and ERRβ breast cancer cell lines. Fluorescence-activated cell sorting analysis (FACS) showed increased G0/G1 phase cell population in ERRβ overexpressed MCF7 cells. Furthermore, ERRβ expression was inversely correlated with overall survival in breast cancer. Collectively our results suggest cell cycle and tumor suppressor role of ERRβ in breast cancer cells which provide a potential avenue to target ERRβ signaling pathway in breast cancer. Conclusion Our results indicate that ERRβ is a negative regulator of cell cycle and a possible tumor suppressor in breast cancer. ERRβ could be therapeutic target for the treatment of breast cancer.